Climate change mitigation and the forest sector (2008)
The paper provides an overview on the global phenomenon of climate change and tile portentous impacts of greenhouse gas (GHG) emission. The international efforts vis-a-vis the UNFCCC and the Kyoto protocol aimed at curbing the effects of climate change were discussed. The role of the forest as a potential climate change mitigation tool was also analyzed while policies for mitigation were appraised. Forests and vegetation cover are seen as an important source of carbon as well as a carbon store. Thus, they can play a key role in generating carbon offsets- the most important GHG being contributed by human activities. The conservation of forests offers important opportunities to mitigate climate change and protect biodiversity. Therefore, the impacts of climate change on human and natural ecosystems can be reduced though the adoption of forest-based conservation strategies. The paper concludes by drawing lessons applicable to tropical African countries.